Islamic Values in Coastal SME Education: A Model for Sustainable Development - Doktoralina, Caturida Meiwanto; Al Faruq Abdullah, Muhamad; Desty Febrian, Wenny; Maulana, Diky; Adi Prayogo, Dhani; Anuar Ahmad Shukor, Ahmad Shaifful (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
AbstractThis study analyses the integration of Maqasid Syariah (MS) principles, including shiddiq (honesty), adl (justice), and maslahah (public welfare), in supporting the sustainability of micro-enterprises (SMEs) in Desa Segara Jaya, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews and observations with Muslim entrepreneurs. SMEs face challenges such as limited financial resources, inadequate Islamic values-based training, and insufficient infrastructure, which hinder the consistent application of ethical practices. To overcome these barriers, an MS-based educational model is required, combining workshop-based training with tailored educational programmes to address these challenges effectively, mentorship programmes with pesantren and madrasahs, and scalable digital learning platforms. Integrating technical and ethical skills helps align business practices with economic objectives and Islamic values. A collaborative Penta helix approach, engaging government, educational institutions, businesses, communities, and media, is essential for overcoming systemic barriers. Applying the MS framework and the Theory of Planned Behaviour, this research contributes to Islamic entrepreneurship studies and offers practical insights for policymakers, educators, and practitioners. Aligning SME operations with ethical principles enhances resilience, competitiveness, and sustainable development in Muslim communities navigating socio-economic challenges.AbstrakPenelitian ini menganalisis integrasi prinsip-prinsip Maqasid Syariah (MS), termasuk shiddiq (kejujuran), adl (keadilan), dan maslahah (kesejahteraan publik), dalam mendukung keberlanjutan usaha mikro kecil dan menengah (UMKM) di Desa Segara Jaya, Indonesia. Dengan menggunakan pendekatan studi kasus kualitatif, data dikumpulkan melalui wawancara mendalam dan observasi terhadap pengusaha Muslim. UMKM menghadapi tantangan seperti keterbatasan sumber daya keuangan, pelatihan berbasis nilai-nilai Islam yang tidak memadai, dan kurangnya infrastruktur, yang menghambat penerapan praktik etis secara konsisten. Untuk mengatasi hambatan ini, diperlukan model pendidikan berbasis MS yang menggabungkan pelatihan berbasis lokakarya dengan program pendidikan yang dirancang khusus, program pendampingan dengan pesantren dan madrasah, serta platform pembelajaran digital yang dapat diskalakan. Integrasi keterampilan teknis dan etis membantu menyelaraskan praktik bisnis dengan tujuan ekonomi dan nilai-nilai Islam. Pendekatan kolaboratif Penta helix yang melibatkan pemerintah, institusi pendidikan, dunia usaha, komunitas, dan media sangat penting untuk mengatasi hambatan sistemik. Dengan menerapkan kerangka kerja MS dan Teori Perilaku Terencana, penelitian ini berkontribusi pada studi kewirausahaan Islam dan memberikan wawasan praktis bagi pembuat kebijakan, pendidik, dan praktisi. Penyelarasan operasional UMKM dengan prinsip-prinsip etis meningkatkan ketahanan, daya saing, dan pembangunan berkelanjutan di komunitas Muslim yang menghadapi tantangan sosial-ekonomi. How to Cite: Doktoralina, C. M., Abdullah, M. A. F., Febrian, W. D., Maulana, D., Prayogo, D. A., & Anuar Ahmad Shukor, A. S. (2024). Islamic Values in Coastal SME Education: A Model for Sustainable Development. TARBIYA: Journal of Education in Muslim Society, 11(2), 105-114. doi:10.15408/tjems.v11i2.43868.